How does STEM context-based learning work: what we know and what we still do not know. Issue 10 (3rd July 2018) - Sevian, Hannah; Dori, Yehudit Judy; Parchmann, Ilka
ABSTRACT: Context-based learning (CBL) has influenced teaching and learning science in many countries over the past decades. Twelve years ago, a special issue on CBL was published in this Journal, focusing on CBL curriculum development. Seven papers in this current special issue on CBL now address the question of how a context influences the learning process. The papers focus on the stimulation of learning STEM subjects within contexts, how the learning process occurs and is enhanced, and the application of contexts in different settings. The approaches, results, and implications of the papers are located in a larger view that considers the question of what must be the case if a student not only engages in the tasks of learning but also succeeds at them. Concerning willingness and effort by learners, the papers draw conclusions about which STEM-related interests of students endure and are ephemeral across a decade, design criteria for maximising students' situational interest, and students' engagement with content and context simultaneously. Focusing on the opportunity to teach and learn, the papers reveal how a professional development approach functions to support STEM teachers to develop CBL materials, and how specific scaffolding acts in teaching bring students to more complex reasoning. Regarding good teaching, insights are offered on how metacognitive prompts improve teaching. Centring on the social surround that supports teaching and learning, a comparison of two contexts for teaching the same content reveals which aspects of the contexts move student learning forward. From this mapping, paths toward future research are projected.